Relationship Between Peroneal Nerve and Anterior Cruciate Ligament Involvement in Multiligamentous Knee Injury: A Multicenter Study. Issue 22 (15th November 2022) - Markus, Danielle H.; Mojica, Edward S.; Bi, Andrew; Kahan, Joseph B.; Moran, Jay; Mannino, Brian J.; Alaia, Erin F.; Jazrawi, Laith M.; Medvecky, Michael J.; Alaia, Michael J.
Abstract : Introduction: Peroneal nerve injuries are rare injuries and usually associated with multiligamentous knee injuries (MLKIs) involving one or both cruciate ligaments. The purpose of our study was to perform a multicenter retrospective cohort analysis to examine the rates of peroneal nerve injuries and to see whether a peroneal nerve injury was suggestive of a particular injury pattern. Methods: A retrospective chart review was conducted in patients who were diagnosed with MLKI at two level I trauma centers from January 2001 to March 2021. MLKIs were defined as complete injuries to two or more knee ligaments that required surgical reconstruction or repair. Peroneal nerve injury was clinically diagnosed in these patients by the attending orthopaedic surgeon. Radiographs, advanced imaging, and surgical characteristics were obtained through a chart review. Results: Overall, 221 patients were included in this study. The mean age was 35.9 years, and 72.9% of the population was male. Overall, the incidence of clinical peroneal nerve injury was 19.5% (43 patients). One hundred percent of the patients with peroneal nerve injury had a posterolateral corner injury. Among patients with peroneal nerve injury, 95.3% had a complete anterior cruciate ligament (ACL) rupture as compared with 4.7% of the patients who presented with an intact ACL. There was 4.4 times of greater relative risk of peroneal nerve injury in the MLKI with ACL tear group compared with the MLKI without an ACL tear group. No statistical difference was observed in age, sex, or body mass index between patients experiencing peroneal nerve injuries and those who did not. Conclusion: The rate of ACL involvement in patients presenting with a traumatic peroneal nerve palsy is exceptionally high, whereas the chance of having a spared ACL is exceptionally low. More than 90% of the patients presenting with a nerve palsy will have sustained, at the least, an ACL and posterolateral corner injury. Level of Evidence: IV, Case Series